Critical Overview on the Benefits and Harms of Aspirin - Chun Shing Kwok; Yoon K. Loke (Pharmaceuticals, 2010)
Aspirin is widely used internationally for a variety of indications, with the most prominent one being that of cardiovascular disease. However, aspirin has also been proposed as a treatment option in a diverse range of conditions such as diabetes mellitus, cancer prevention, and obstetrics. In our overview, we critically appraise the current evidence from recent systematic reviews and meta-analyses covering the benefits of aspirin across these conditions. We also look at evidence that some patients may not derive benefit due to the concept of aspirin resistance. Aspirin is also associated with the potential for significant harm, principally from haemorrhagic adverse events. We critically appraise the threat of haemorrhagic complications, and weigh up these risks against that of any potential benefit.